(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
At present, the problem of searching for alternative energy sources and promising ways of resource saving is urgent and is becoming one of the main ones for the development economy of states. In this regard, it is important to research and develop technologies that ensure the integrated use of raw materials and environmental safety of production [1]. Waste from the coal industry, the fat-and-oil industry, and the processing of agricultural products can be turned into high-quality fuel raw materials. In this regard, research and development are under way in many countries, resulting in new types of fuels